Training on Oral Drug Administration in Test Animals as an Effort to Strengthen Pharmacology Practicum Competence - Prasetyawan, Fendy; Saristiana, Yuneka; Salmasfattah, Novynanda; Alshol, Mohammad Firdaus (Mitra Jurnal Pengabdian Masyarakat Multidisiplin (MJPMM), 2025)
Training in the skill of administering oral medication to test animals is a form of community service aimed at enhancing pharmacy students' competencies in pharmacology laboratory practices. This activity will take place on May 19, 2025, in the Pharmacology Laboratory at Kadiri University. It will consist of direct training that includes theoretical presentations, demonstrations, and independent practice by students, accompanied by guidance from instructors and laboratory staff. The materials presented include the anatomy of the mouse digestive system, the basic principles of oral gavage, the ethics of using test animals, and safety aspects. The evaluation results indicate that this training has enhanced the participants' understanding of oral gavage techniques as well as their skills in performing the procedure safely and accurately. Based on the comparison of pretest and posttest scores, as well as practical observations, there is a significant improvement in the technical skills and ethical attitudes of the students. This training also enhances the understanding of the importance of animal welfare in pharmacological experiments. This activity is expected to serve as a sustainable model for enhancing the quality of practical learning in the field of pharmacy education.